Concise synthesis of (+/-)-clopidogrel via carboxylation of benzylamine with CO2 - Venkataramasubramanian, V.; Sudalai, Arumugam (Synthetic Communications, 2015)
A concise and efficient synthesis of (+/-)-clopidogrel, an antithrombotic agent, is achieved by inserting CO2 at the benzylic position as the key reaction without using any toxic transition metals. The overall yield of the synthetic process is 38% and the salient features include operationally simple process chemistry and fewer steps.
Keywords: Antithrombatic agent; clopidogrel; CO2 insertion; Plavix